STUDY OF THE SWELLING OF THE PHOSPHOLIPID BILAYER, DEPENDING ON THE ANGLE BETWEEN THE INCLINATION OF THE DIPOLE FRAGMENTS AND THE PLANE OF THE LAMELLA - Stepanyan, M.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
Using computer simulations and simultaneous X-ray diffraction at large and small angles, the dependence of the swelling coefficient of the phospholipid bilayer on the angle between the inclination of dipole fragments and the plane of the lamella was investigated. It was shown that in this case the balance between electrostatic, repulsive and van der Waals attraction forces is a particular importance. As the dipole angle increases, the repulsive forces of the electrostatic dipole-dipole interaction increase, resulting the increase of the bilayer thickness as a function of the number of –CH-groups in the phospholipid. At a certain angle the bilayer is destroyed. It is also shown that at certain small angles the bilayer takes a minimum thickness. In this case a phase transformation takes place and the system enters the “gel”-phase.
Keywords: phospholipid bilayer; lamella; dipole fragment; swelling